2010
DOI: 10.1186/1754-9493-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Complications in colorectal surgery: risk factors and preventive strategies

Abstract: BackroundOpen or laparoscopic colorectal surgery comprises of many different types of procedures for various diseases. Depending upon the operation and modifiable and non-modifiable risk factors the intra- and postoperative morbidity and mortality rate vary. In general, surgical complications can be divided into intraoperative and postoperative complications and usually occur while the patient is still in the hospital.MethodsA literature search (1980-2009) was carried out, using MEDLINE, PubMed and the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
238
2
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(283 citation statements)
references
References 118 publications
11
238
2
11
Order By: Relevance
“…The various surgical methodologies, procedures performed, and patient samples across the studies is a limitation of this review and leads to a high level of variability across the sample, which likely accounts for the wide range of intra-operative (0.0% -23.3%) and post-operative (0.8% -15.0%) leak rates observed across studies. Further, as noted in other studies, the definition for anastomotic leak and other postoperative complications varies across surgical sites and institutions reducing the level of accuracy in estimating anastomotic leak rates [35,40]. Although 10 articles had a similar definition of anastomotic leak there were six slightly different definitions for anastomotic leak; further three manuscripts did not provide a definition for anastomotic leak.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The various surgical methodologies, procedures performed, and patient samples across the studies is a limitation of this review and leads to a high level of variability across the sample, which likely accounts for the wide range of intra-operative (0.0% -23.3%) and post-operative (0.8% -15.0%) leak rates observed across studies. Further, as noted in other studies, the definition for anastomotic leak and other postoperative complications varies across surgical sites and institutions reducing the level of accuracy in estimating anastomotic leak rates [35,40]. Although 10 articles had a similar definition of anastomotic leak there were six slightly different definitions for anastomotic leak; further three manuscripts did not provide a definition for anastomotic leak.…”
Section: Discussionmentioning
confidence: 91%
“…Although the definitive causes of post-operative anastomotic leak remains unknown, leak development is believed to be related to anastomotic healing, as opposed to intraoperative leaks which are the result of injury, adhesions, and weak or insufficient anastomosis, related to factors of the surgery itself [35]. Therefore, aside from a minority of cases where an undetected or uncorrected intra-operative leak progresses to a clinical post-operative leak, there is no reason to assume there is a direct relationship between the development of intra-operative and post-operative leaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent postoperative surgical complications after colorectal resections are surgical site infection, anastomotic leakage, intraabdominal abscess, ileus and bleeding (5).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Kirchhoff et al, 2010 reported damage to the spleen (incidence of 0.006%), or intestinal perforation and ureteric injuries (incidence < 0.01%) [14].…”
Section: Variablesmentioning
confidence: 99%